Ramsay Hunt syndrome - Michał Perszke; Dominika Egierska (Kazimierz Wielki University, 2022)
Ramsay-Hunt syndrome (RHS) is a disease caused by reactivation of varicella-zoster  virus in the geniculate ganglion. It may be one of the common reasons of the facial palsy. Symptoms of the RHS include vesicular rash on the auricle, external auditory canal, soft palate, pharynx, facial nerve paralysis, ear pain, tinnitus, vertigo and hearing loss. There may be other symptoms connected to cranial nerves (CN) V, VIII, IX or X, when they are involved.  Men are more likely to develop lesions than women. Risk of developing Ramsay-Hunt syndrome increases with age. Authors searched Google Scholar and PubMed, using searchterms Ramsay-Hunt syndrome, varicella-zoster virus, VZV, facial palsy. We manually searched the references of selected articles for additional relevant articles. We selected articles relevant to a general medicine readership and prioritised systematic reviews, clinical practice guidelines and cases. The literature contains the latest reports on Ramsay-Hunt syndrome. Clinicians should not ignore patients' symptoms and always pay attention to possibility of VZV infection and the development of RHS, as treatment should be started within 72 hours after the onset of the symptoms. Main treatment includes antiviral drugs and corticosteroids. The results are promising.